In Defense of Globalization - Jagdish N. Bhagwati (New York Oxford University Press, 2007)
In the passionate debate that currently rages over globalization, critics have been heard blaming it for a host of ills afflicting poorer nations, everything from child labor to environmental degradation and cultural homogenization. Now Jagdish Bhagwati, the internationally renowned economist, takes on the critics, revealing that globalization, when properly governed, is in fact the most powerful force for social good in the world today. Drawing on his unparalleled knowledge of international and development economics, Bhagwati explains why the gotcha examples of the critics are often not as compelling as they seem. With the wit and wisdom for which he is renowned, Bhagwati convincingly shows that globalization is part of the solution, not part of the problem. This edition features a new afterword by the author, in which he counters recent writings by prominent journalist Thomas Friedman and the Nobel Laureate economist Paul Samuelson and argues that current anxieties about the economic implications of globalization are just as unfounded as were the concerns about its social effects.
Keywords: Globalization; Economics; Nonfiction; Politics; International relations; Global Citizenship (BIN1064-N)